Application of The Analytic Hierarchy Process (AHP) in Strategic Factory Selection for Putra Madura Sejati Cigarette Company in Pamekasan - Muhammad, Rayyan; Susanti, Rina; Rosyadi NR , Imron (Tibuana, 2026)
The tobacco industry in Indonesia is developing rapidly. Indonesia itself is the fifth largest tobacco producing country. Cigarettes are one of the sectors that contribute the most to excise and foreign exchange revenues for the country. With the rapid growth of the cigarette industry, producers must design good strategies to continue to compete and develop in this cigarette industry, one of which is finding a strategic factory location for consumer satisfaction. The purpose of this study is to find the best location for the PR Putra Madura Sejati cigarette factory based on the criteria of accessibility, environment, workforce, market, and traffic. And the alternative locations that will be selected in this research are located in Pamekasan district, namely on Blumbungan Street, Bangunran Street, Larangan Street, and Pademawu Street. The method used this time is the Analytical Hierarchy Process (AHP). Based on the results of the pairwise comparison between the criteria, this time it shows that the accessibility criterion has a value of 0.09, the environment has a value of 0.23, the workforce has a value of 0.47, the market has a value of 0.05, and traffic has a value of 0.16. then the results of the pairwise comparison between the accessibility criteria with all alternatives obtained the nyalaran road alternative has the highest value with 0.59, environmental criteria with the alternative namely nyalaran road highest with 0.53, workforce criteria with the alternative namely blumbungan road highest with 0.49, market criteria with the alternative namely pademawu road with 0.49, and traffic criteria with the alternative namely nyalaran road with 0.52. The final result of the pairwise comparison between all alternatives and all criteria shows that Jalan nyalaran is the best location to be selected with a value of 41.6. The author advises PR Putra Madura Sejati to continue implementing strategies by getting closer to the market and selecting skilled workers so that the quality of the cigarettes created will be better and can provide satisfaction to consumers.